Predictive imaging biomarkers relevant for functional and anatomical outcomes during ranibizumab therapy of diabetic macular oedema. Issue 2 (19th July 2017) - Gerendas, Bianca S; Prager, Sonja; Deak, Gabor; Simader, Christian; Lammer, Jan; Waldstein, Sebastian M; Guerin, Tadhg; Kundi, Michael; Schmidt-Erfurth, Ursula Margarethe
Abstract : Background/aims: The objective is to identify imaging biomarkers in optical coherence tomography predicting functional/anatomical outcomes in diabetic macular oedema (DMO). Methods: The presented study is a post hoc analysis of the RESTORE/RESTORE-extension studies. Best-corrected visual acuity (BCVA) was analysed using general estimating equation models using treatment group/morphological features as predictor variables. In addition, linear multiple regression models analysed BCVA gain up to 12 and 36 months with BCVA/morphological baseline characteristics as independent predictor variables. The correlations between central retinal thickness (CRT)/BCVA were calculated as Spearman's/Pearson's correlation coefficients. Results: A weak negative linear correlation between CRT/BCVA was observed in all study arms at baseline (r=−0.34, p<0.001) and at month 36 (r=−0.26, p<0.001). Patients with baseline height of intraretinal cystoid fluid (IRC) ≤380 µm had better baseline BCVA compared with patients with IRC height >380 µm (64.84±10.63 vs 61.66±9.92 letters; p=0.0071, respectively), which was maintained until the end of month 12 (70.5±12.33 vs 67.0±14.09 letters; p=0.0252, respectively). With laser, there was a trend for patients with subretinal fluid (SRF) at baseline to lose BCVA letters at month 12 (−5.38±16.54 vs 2.49±9.72 letters; p=0.1038), whereas ranibizumab patients trended towards higher BCVA gains (10.28±7.14 vs 6.76±7.67; p=0.0563), compared with those without SRF. With combined therapy, all patients had similar BCVA gains regardless of SRF (p=0.3768). Conclusion: With ranibizumab treatment, the height of IRC spaces at baseline was a better predictor of functional/anatomical improvement than CRT alone. There was also a trend for SRF to show a positive impact on ranibizumab therapy response and a negative impact on laser therapy response.